Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1021/acs.iecr.7b01855
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Current Generation Using Mutualistic Interaction of Yeast-Bacterial Coculture in Dual Chamber Microbial Fuel Cell

Abstract: Although exogenous mediators can distinctly enhance the performance of yeast driven microbial fuel cell (MFC), the possibility of mediator's toxicity, environmental risk, and cost are the main challenges facing toward its application in MFCs. Therefore, the use of naturally produced electron shuttles for unmediated yeast would be of great interest since it can solve most of the above-mentioned problems. The present study is to investigate the possibility of the use of electron shuttle producing bacteria Klebsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 48 publications
(27 citation statements)
references
References 45 publications
0
27
0
Order By: Relevance
“…Klebsiella pneumonia was another strain that could secrete electron mediators. The MFC constructed by co-culture of Klebsiella pneumonia and Lipomyces starkeyi produced a peak power density of 12.87 W/m 3 [97].…”
Section: Mixed Communities As Electricigens In the Anodementioning
confidence: 99%
“…Klebsiella pneumonia was another strain that could secrete electron mediators. The MFC constructed by co-culture of Klebsiella pneumonia and Lipomyces starkeyi produced a peak power density of 12.87 W/m 3 [97].…”
Section: Mixed Communities As Electricigens In the Anodementioning
confidence: 99%
“…Enhanced current generation using yeast-bacterial coculture was observed by Islam et al [64]. The power production in MFCs, which inoculated the yeast Lipomyces starkeyi with Klebsiella pneumoniae was 3-6 times higher (12.87 Wm −3 ) in comparison to MFCs using bacteria or yeast separately.…”
Section: Other Speciesmentioning
confidence: 86%
“…Moreover, it showed that live-cell mass are needed rather than thick biofilm to obtain higher metabolic activity as well as higher current generation. Our previous study [33] also showed that the redox peak significantly reduced due to the formation of multilayer biofilm comprising more dead cells, and this dead inner layer hindered the electron transfer from the live bacteria present in the outer layer of the biofilm and bulk solution. Besides that, the electrons in the biofilm needed to travel over substantial distances to reach the anode and the resistance associated with long distance electron transport is substantially higher than the resistance associated with the single electron transfer step from the biofilm to the anode at the biofilm/anode interface [34].…”
Section: Accepted Manuscriptmentioning
confidence: 88%